2005
DOI: 10.1002/ecjc.20147
|View full text |Cite
|
Sign up to set email alerts
|

Category recognition system using two ultrasonic sensors and combinational logic circuit

Abstract: SUMMARYIn this paper, we employ a technique that is used to recognize a material from the reflected ultrasonic waves and propose a category recognition system using two ultrasonic sensors. In this system, the reflected waveforms are handled as two-dimensional images, and which category an object belongs to is instantaneously recognized by pattern matching to reference data by a combinatorial logic circuit. In this system, combinations of information such as the material, angle, and distance of the object are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In our target task of reverse vending machines, the object material is important. It has been shown that material classification is viable with ultrasonic signals [42,43], so we decided to use ultrasonic sensors as a new modality.…”
Section: Cmu-mosi and Cmu-moseimentioning
confidence: 99%
See 1 more Smart Citation
“…In our target task of reverse vending machines, the object material is important. It has been shown that material classification is viable with ultrasonic signals [42,43], so we decided to use ultrasonic sensors as a new modality.…”
Section: Cmu-mosi and Cmu-moseimentioning
confidence: 99%
“…However, the experiments conducted in [42,43] were highly controlled in that the target objects were flat board shapes with the same pose and distance from the sensors. In real-world cases, the target objects would be in various shapes, sizes and poses.…”
Section: Cmu-mosi and Cmu-moseimentioning
confidence: 99%
“…However, these methods are unable to detect dangerous ground surfaces. Furthermore, studies also examined material distinction characteristics [7,8]. The methods examined the reflected waveform as a 2D image, and introduced a pattern-matching approach based on benchmark patterns.…”
Section: Introductionmentioning
confidence: 99%